PEMBELAJARAN SEJARAH TERINTEGRASI NILAI-NILAI KEISLAMAN DI MADRASAH ALIYAH NEGERI 1 LAMPUNG TIMUR - Ria Ratna Sari; Kian Amboro (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The purpose of this study is to describe the history of learning integrated Islamic values class XI IPS 1 semester even in MAN 1 Lampung Timur. Where this research is a type of qualitative research by using descriptive approach. Data collection techniques used by researchers is by in-depth interviews, observations and documentation. Data analysis technique conducted by the first researcher to reduce the data after that done the presentation of data after that do verifikasion. The results of this study indicate that the history teacher to do learning integrated history of Islamic values quite well. This can be seen from the teachers doing the planning process by making the RPP integrated with Islamic values, the process of learning in the classroom, the evaluation process undertaken by teachers and constraints faced by teachers in learning the history of integrating Islamic values. With the curriculum implemented by MAN 1 Lampung Timur school that is the 2013 curriculum in every process of learning the integration of teachers always adjust to the curriculum and vision of school mission. The purpose of teachers to learn the integration of Islamic values is to strengthen the faith of students in the school environment and in the community. In addition, in the process of learning the integration of Islamic values is expected to realize the vision and mission of MAN 1 Lampung Timur.